Better prognosis in females with severe COVID-19 pneumonia: possible role of inflammation as potential mediator - Mussini, Cristina (Clin Microbiol Infect, 2021)
OBJECTIVES: Sex differences in COVID-19 severity and mortality have been described. Key aims of this analysis were to compare the risk of invasive mechanical ventilation (IMV) and mortality by sex and to explore whether variation in specific biomarkers could mediate this difference. METHODS: This was a retrospective, observational cohort study among patients with severe COVID-19 pneumonia. A survival analysis was conducted to compare time to the composite endpoint of IMV or death according to sex. Interaction was formally tested to compare the risk difference by sex in sub-populations. Mediation analysis with a binary endpoint IMV or death (yes/no) by day 28 of follow-up for a number of inflammation/coagulation biomarkers in the context of counterfactual prediction was also conducted. RESULTS: Among 415 patients, 134 were females (32%) and 281 males (67%), median age 66 years (IQR 54–77). At admission, females showed a significantly less severe clinical and respiratory profiles with a higher PaO(2)/FiO(2) (254 mmHg vs. 191 mmHg; p 0.023). By 28 days from admission, 49.2% (95% CI 39.6–58.9%) of males vs. 31.7% (17.9–45.4%) of females underwent IMV or death (log-rank p < 0.0001) and this amounted to a difference in terms of HR of 0.40 (0.26–0.63, p 0.0001). The area under the curve in C-reactive protein (CRP) over the study period appeared to explain 85% of this difference in risk by sex. DISCUSSION: Our analysis confirms a difference in the risk of COVID-19 clinical progression by sex and provides a hypothesis for potential mechanisms leading to this. Specifically, CRP showed a predominant role to mediate the difference in risk by sex.